Outpatient Minimally Invasive Lumbar Interbody: Fusion Predictive Factors and Clinical Results. (April 2016) - Smith, William D.; Wohns, Richard N. W.; Christian, Ginger; Rodgers, Evelyn J.; Rodgers, W. Blake
Abstract : Study Design: Retrospective review of data from a prospective patient outcomes registry. Objective: The object of this work was to examine patient and surgical predictors of early postoperative discharge and test the predictive model against two clinical series of outpatient minimally invasive lumbar fusion patients. Summary of Background Data: Outpatient and ambulatory surgery centers are regularly utilized for procedures with low-risk profiles and minimal need for extended postoperative observation, but little has been reported in lumbar spinal fusion producers. Methods: Two analyses were undertaken, an examination of patient characteristics to determine predictors of early (<24 hours) postoperative discharge and then clinical examinations of patients treated with lumbar fusion at an ambulatory surgery center. For the predictive arm of the study, 1033 patients treated with minimally invasive (MIS) lateral interbody fusion (XLIF) were grouped according to length of postoperative hospitalization with 873 patients discharged <24 hours (outpatients), and 160 discharged >23 hours after surgery (inpatients). For the clinical studies, 54 consecutive XLIF and 18 consecutive MIS posterior fusion patients were treated at an ambulatory surgery center with demographic, treatment, and complication data collected. Results: From the predictive study, the strongest baseline predictors of early postoperative discharge were a less advanced diagnosis (non-deformity), younger age, elevated baseline hemoglobin levels, and lower body mass index. The most predictive treatment variables that predicted early postoperative discharge were fewer number of levels treated and elevated postoperative hemoglobin levels. In the clinical series, outpatient surgeries were performed in younger patients (50.6 and 53.2 yr), at relatively few levels (96% of cases were at one or two levels), for simple degenerative disease. No intraoperative and few postoperatives complications were seen in either XLIF or MIS posterior fusions performed in ambulatory settings with no emergent transfers to inpatient facilities. Conclusion: Select patients, by health and indication, can safely be treated as outpatients with XLIF or other modern MIS approaches. Being younger, having elevated preoperative hemoglobin levels, fewer levels being treated, for less advanced disease may predict early postoperative discharge. Level of Evidence: 3